ANALISIS USER EXPERIENCE PADA APLIKASI ALPUKAT BETAWI (AKSES LANGSUNG PELAYANAN DOKUMEN KEPENDUDUKAN CEPAT DAN AKURAT) DENGAN MENGGUNAKAN METODE COGNITIVE WALKTHROUGH DAN METODE USER EXPERIENCE QUESTIONNAIRE - Muhammad Riza Akbar Pramudya (2022)
Alpukat Betawi is a website and mobile-based information system created and developed by the DKI Jakarta Provincial Dukcapil Office. In the Alpukat Betawi application, the public can take care of population documents. The number of users on an application does not rule out the possibility of dissatisfaction in using the application. For this reason, it is necessary to analyze the Alpukat Betawi application using the cognitive walkthrough method and the user experience questionnaire method. The purpose of the research carried out is to analyze and identify problems or difficulties experienced by users by completing the task scenarios given in this study, then recommendations for interface improvements in the form of prototype designs will be given to the Alpukat Betawi application.. The results of this study are that there are many difficulties experienced by respondents when completing task scenarios and the results of the six user experience questionnaire (UEQ) assessment scales are below the average value and it is necessary to improve the quality of the Alpukat Betawi application by providing a new look, resulting in recommendations for improvement. interface based on the problems and difficulties faced by respondents.